Freising and Worms in the early eleventh century revisiting the relationship between the "Collectio duodecim partium" and Burchard's "Decretum" - Austin, Greta (2007)
Burchard von Worms, Liber decretorum (Decretum), Freising, Collectio duodecim partium.
Keywords: Dekretalen; Dekretalen; Recht; Geschichte; Rechtssammlung